THE NEW MISDEMEANOR LAW AND OLD ISSUES WITH SECURITY MEASURES ORDERING COMPULSORY ALCOHOL AND DRUG ADDICTION TREATMENT - Milić, Ivan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The introductory part of this paper presents the basic changes to the Misdemeanor law, which is in force since March 1. 2014. At the begining of the paper we will describe the security measures which can be ordered to offeneders and highlight some changes in this area that have been prescribed by the new law. Next we will point out certain issues which may arise when ordering compulsory alcohol and drug addiction treatment. While a new law has been passed which, among other things, increases the number of available security measures, the old issues still persist when the above mentioned security measures are concerned. Special consideration will be given to whether the security measures should be carried out in at an institution or at liberty, which is a crucial question when ordering compulsory alcohol and drug addiction treatment.